An Analysis of Slang Words in Star Wars Jedi Academy: The Force Oversleep - Debora Natalia Hutabarat (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
This thesis is study about the types and the meaning of each slang words in Star Wars Jedi Academy: The Force Oversleep. The theory supported this analysis is Eric Partridge theory (2004) which explain about types of slang words. This thesis is designed as library research, in which the methodology used in this thesis is qualitative description method. The data contained in this thesis is taken from the words which contained in slang words in Star Wars Jedi Academy: The Force Oversleep storybook, the data is taken from whole pages, start from page 6 until page 172. The result of this analysis found 2 types of slang words, (1) Public School and University, and (2) Society Slang. The researcher explained the meaning of each slang words based on context. Keywords: Sociolinguistics, Slang, Types of Slang, Eric Partridge, Storybook.